Analisis Sosio-Legal terhadap Faktor Penyebab dan Dampak Pernikahan di Bawah Umur - Ummah, Rahmatul; Widiyanto, Hari; Abqori, Najih (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study looks at the problem of underage marriage, which is still prevalent in Malang Village, Ngombol District, Purworejo Regency. The rise in early marriages, which has resulted in several home and social problems, provides the background for this study. The purpose of this study is to determine the reasons behind early marriage and the consequences it has on both couples and society. Data for this study is gathered through documentation, interviews, and observation using a qualitative technique. The results show that the main factor causing underage marriage is the influence of promiscuity, other factors are economic, low levels of education, and weak parental supervision. The resulting impacts include emotional unpreparedness that triggers domestic conflict, an increase in divorce rates, and limited opportunities for women to develop in the educational and economic fields. Socially, this phenomenon raises concerns about the future of the younger generation. Therefore, preventive efforts are necessary through socialization and legal counseling regarding the minimum age for marriage as regulated in Law Number 16 of 2019 concerning Marriage. Cooperation between village governments, educational institutions, religious leaders, and the community is key to reducing the number of underage marriages.